Hfq and sRNA 179 Inhibit Expression of the Pseudomonas aeruginosa cAMP-Vfr and Type III Secretion Regulons - Kayley H. Janssen; Jodi M. Corley; Louise Djapgne; J. T. Cribbs; Deven Voelker; Zachary Slusher; Robert Nordell; Elizabeth E. Regulski; Barbara I. Kazmierczak; Emily Williams McMackin; Timothy L. Yahr (mBio, 2020)
ABSTRACT Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen causing skin and soft tissue, respiratory, and bloodstream infections. The type III secretion system (T3SS) is one important virulence factor. Production of the T3SS is controlled by ExsA, a transcription factor that activates expression of the entire T3SS regulon. Global regulators including Vfr, RsmA, and Hfq also contribute to regulation of the T3SS. Vfr is a cAMP-responsive transcription factor that activates exsA transcription. RsmA, an RNA-binding protein, inversely controls expression of the T3SS and the type VI secretion system (T6SS). Hfq is an RNA chaperone that functions by stabilizing small noncoding RNAs (sRNAs) and/or facilitating base pairing between sRNAs and mRNA targets. A previous study identified sRNA 1061, which directly targets the exsA mRNA and likely inhibits ExsA synthesis. In this study, we screened an sRNA expression library and identified sRNA 179 as an Hfq-dependent inhibitor of T3SS gene expression. Further characterization revealed that sRNA 179 inhibits the synthesis of both ExsA and Vfr. The previous finding that RsmA stimulates ExsA and Vfr synthesis suggested that sRNA 179 impacts the Gac/Rsm system. Consistent with that idea, the inhibitory activity of sRNA 179 is suppressed in a mutant lacking rsmY and rsmZ, and sRNA 179 expression stimulates rsmY transcription. RsmY and RsmZ are small noncoding RNAs that sequester RsmA from target mRNAs. Our combined findings show that Hfq and sRNA 179 indirectly regulate ExsA and Vfr synthesis by reducing the available pool of RsmA, leading to reduced expression of the T3SS and cAMP-Vfr regulons. IMPORTANCE Control of gene expression by small noncoding RNA (sRNA) is well documented but underappreciated. Deep sequencing of mRNA preparations from Pseudomonas aeruginosa suggests that >500 sRNAs are generated. Few of those sRNAs have defined roles in gene expression. To address that knowledge gap, we constructed an sRNA expression library and identified sRNA 179 as a regulator of the type III secretion system (T3SS) and the cAMP-Vfr regulons. The T3SS- and cAMP-Vfr-controlled genes are critical virulence factors. Increased understanding of the signals and regulatory mechanisms that control these important factors will enhance our understanding of disease progression and reveal potential approaches for therapeutic intervention.